PENGARUH KEGIATAN EKSTRAKURIKULER ROHANI ISLAM (ROHIS) TERHADAP KEMAMPUAN MEMBACA Al-QUR’AN SISWA KELAS X SMA NEGERI 1 KOTO SALAK KABUPATEN DHARMASRAYA - Ela Oktaviani; Supriadi Supriadi; Jasmienti Jasmienti; Nurhasnah Nurhasnah (STIKes Ibnu Sina Ajibarang, 2023)
This research was motivated by the low ability to read the Qur’an in class X SMA Negeri 1 Koto Salak. This study aims to determine how much influence “Islamic Spritual Extracurricullar Activities (Rohis) have on the ability to read the Al-Qur’an of Class X Student of SMA Negeri 1 Koto Salak, Dharmasraya Regency”. This research is a correlational study using quantitative data trends. The population in this study amounted to 132 students consisting of five classes. The sample used in the study amounted to 40 students, with the sampling technique this is probability sampling. The data analysis technique used in the normality test, linearity test and hypotehesis testing. The results showed that the calculation of the T-Test with a significance level of 5%, obtained a t (count) value of 5.059 > t-table 2.026, then H0 was rejected and Ha was accepted, so it can be concluded that Spritual Activity (X) has a positive and significant effect on Al-Qur’an Reading Ability Student Qur’an (Y). The contribution of spritual extracurricular activities to the ability to read the Qur’an was 40,2 %, while the remaining 59,8 % was influenced by other factors not examined in this study. So the correlation coefficient is at a moderate level, because it is in the coefficient interval between 0.400-0,599.